FASTING IN HYBRID GROUPER EPINEPHELUS FUSCOGUTTATUS X EPINEPHELUS LANCEOLATUS IN RELATION TO PROXIMATE CONTENTS, GROWTH AND FEED EFFICIENCY - Asih, Yasmina Nirmala; Mahardika, Ketut; Susanto, Bambang (Marine Research in Indonesia, 2019)
Fasting in fish was used to improve quality of fish product post-slaughtered. The aims of the study were to investigate alteration of nutrition contents, growth and feed efficiency of hybrid grouper fasted on certain day intervals. There were two experiments in this study; the first experiment was to evaluate alteration nutrient contents of carcasses and livers of hybrid grouper. The fish were grouped into 3 feeding regimes. Group of fish one (n=50) were fed daily. Group of fish two (n=50) were fasted on one day interval. Fish of group three (n=50) were fasted on two days interval. The second experiment was to evaluate growth and feed efficiency of the fish. Hybrid grouper were subjected to two feeding regimes. Group of fish one (n=45) were fed daily and group of fish two (n=45) were fasted on two days interval. The first and second experiments were conducted for one and two months, respectively. The results showed that hybrid grouper fed daily had the lowest protein and the highest fat in the carcass compared to those fasted on one or two days interval. In the first month, there was no difference between growth rate of the fish fed daily and fasted on two days interval (32.88 and 32.08%, respectively). However, in the second month, the fish fed daily (66.08%) had 1.4 times higher growth rate than those fasted on two days interval (48.12%). To sum up, fasting in hybrid grouper could alter proximate contents, slow down growth and improve feed efficiency.